2022
DOI: 10.1038/s41396-022-01352-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of direct physical association and motility on fitness of a synthetic interkingdom microbial community

Abstract: Mutualistic exchange of metabolites can play an important role in microbial communities. Under natural environmental conditions, such exchange may be compromised by the dispersal of metabolites and by the presence of non-cooperating microorganisms. Spatial proximity between members during sessile growth on solid surfaces has been shown to promote stabilization of cross-feeding communities against these challenges. Nonetheless, many natural cross-feeding communities are not sessile but rather pelagic and exist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 78 publications
(84 reference statements)
2
11
0
Order By: Relevance
“…Fluorescence microscopy analysis replicated previous findings 50 showing that adding mannose to growth media prevented most bacteria-yeast clumping (Fig 3a). Image analysis demonstrated that the size of yeast clumps—a proxy for number of yeast cells per clump—increased concurrent with the number of bacteria in a clump (“coincident bacteria”), implying that bacteria mediate cell clump formation (SF5, SF6).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Fluorescence microscopy analysis replicated previous findings 50 showing that adding mannose to growth media prevented most bacteria-yeast clumping (Fig 3a). Image analysis demonstrated that the size of yeast clumps—a proxy for number of yeast cells per clump—increased concurrent with the number of bacteria in a clump (“coincident bacteria”), implying that bacteria mediate cell clump formation (SF5, SF6).…”
Section: Resultssupporting
confidence: 88%
“…Since IDC depends on cell-cell collisions in culture, we explored how known adherence mechanisms between E. coli and S. cerevisiae affect IDC. Mannoproteins are ubiquitous in fungal cell walls 57 , and type I fimbriae in E. coli bind to these 58,59 , forming bacteria-yeast “clumps” that can affect crossfeeding dynamics 50 . We thus repeated our batch culture experiments for population dynamics and IDC with- and without mannose added to the media, which saturates bacterial mannose receptors and reduces clumping.…”
Section: Resultsmentioning
confidence: 99%
“…Close spatial proximity is essential for effective cross-feeding, and the acquisition of metabolites is a key factor for aggregate formation . Although metabolites are highly dispersible and equally distributed in well-mixed environments, , some costly metabolites (i.e., vitamins, amino acids) of FC might be instantly consumed by the surrounding bacteria. To obtain access to valuable phytoplankton products, some bacteria actively move to the phytoplankton surface. ,, This is consistent with the enhanced expression of chemotaxis and flagellar assembly-related genes of symbiotic bacteria with motility (PRO1 and PRO5) in Rf (Figure S11).…”
Section: Discussionmentioning
confidence: 99%
“…11,15,16 For example, in a model bipartite cross-feeding community between bacteria and yeast auxotrophs, flagella mediated the adhesion of two microorganisms to promote local metabolite exchange within the coaggregates, providing fitness benefits to bacterial partners, and counteracted the invasion of the community by uncooperative deceptive strains. 17 By constructing a metabolic model, A. R. Pacheco et al found that costless metabolite cross-feeding enhanced growth capacities, offset nutrients competition, and produced stable interaction motifs. 11 It seems that using two or more microorganisms to treat multiple pollutants will achieve a better performance than a sole microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, microorganisms usually exist in the environment in the form of coexistence with other ones, and each microbe obtains its own favorable niche through interspecific communication and interaction. When encountering some external pressure (e.g., the presence of pollutants or unfavorable growth or metabolic conditions), different microorganisms in the environment often cooperate with each other to improve the pressure situation by reducing the metabolic burden and increasing tolerance to environmental challenges through inherent trade-offs, such as division of labor and resource exchange. ,, For example, in a model bipartite cross-feeding community between bacteria and yeast auxotrophs, flagella mediated the adhesion of two microorganisms to promote local metabolite exchange within the coaggregates, providing fitness benefits to bacterial partners, and counteracted the invasion of the community by uncooperative deceptive strains . By constructing a metabolic model, A. R. Pacheco et al found that costless metabolite cross-feeding enhanced growth capacities, offset nutrients competition, and produced stable interaction motifs .…”
Section: Introductionmentioning
confidence: 99%